Pemberdayaan Masyarakat melalui Sekolah Rimbawan Kecil di Desa Ciranjeng, Kabupaten Majalengka - Dinda Emmy Gusti Sofhia; Anita Julinah; Dina Nurdinawati; Yayat Heryatno; Risda Rizkillah; Melani Abdul Kadir (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
One of the efforts in conservation of conservation areas is through conservation education. Implementation of conservation education that is given in a sustainable manner to the community, is expected to provide conditions for change for the community to have knowledge and skills on how to preserve the environment. Rimbawan Kecil School (Serincil) is a program that aims to provide knowledge to elementary school students in the village of Ciranjeng about the importance of preserving the environment, which is one way to tackle the problem of waste. The purpose of this program is that students can understand and understand the types and dangers of waste and students can apply the 3R concept (Reuse, Reduce and Recycle). This community service activity consists of two series, including the provision of materials from the 2019 IPB University team on the importance of environmental sustainability and the selection of waste materials based on their type in class, as well as the practice of making trash bins from used buckets. Keywords: Conservation, education environment, waste